Performance e envolvimento de jogo: o impacto do híbrido Modelo de Educação Desportiva - Modelo de Competência para Jogos de Invasão em uma unidade didática de andebol
This study aimed to examine the impact of a hybrid teaching model, composed of the Sport Education Model and the Invasion Games Competency Model, on students' learning of handball. The participants in this study were 24 students (16 boys and 8 girls), aged between 10 and 12 years-old, from a public school located in the north of Portugal. Data were collected from recorded videotape images collected during physical education lessons and were treated statistically in the SPSS version 24 program. The game assessment instrument used in this study was based on the protocols used by Tallir et al. (2007), which were grounded on the Game Performance Assessment Instrument created by Oslin et al. (1998). Means and standard deviation values were computed for each game variable assessed. As the data showed no normality, differences between pre-test to post-test scores were computed by using a non-parametric Wilcoxon Test. The students improved both their game performance and game involvement from pre-test to post-test. In parallel with findings of previous research, the hybrid model used in this study was efficient in the promotion of game performance and game involvement. Future research should use more longitudinal research designs and combine quantitative and qualitative methods to reach a deeper understanding of students' performance development.